First lithological and organic geochemical characterization of organic rich mudstones from Shavar Formation, southeast Bulgaria. Issue 1 (31st March 2022) - Zdravkov, Alexander; Ajdanlijsky, George; Stefanova, Maya; Groß, Doris; Dintchev, Yaroslav
ABSTRACT: The paper reports the first results of the organic geochemical characterization of mudstones from the Shavar Fm (eastern Rhodope Mt., Bulgaria). The rock matrix is unevenly impregnated by amorphous organic matter at the onset of the oil generation (Tmax 445ºC; PI – 0.1–0.2). High total organic carbon contents (avg. TOC – 5.9 wt. %) and HI ( 720 mg HC/g TOC) argue for oil-prone source-rocks with very good hydrocarbon potential. The n -alkane distributions with maxima in the range n -C20-25 are consistent with organic matter origin from submerged plants. Additionally, sterane distributions dominated by C28-30 4-methyl steranes, indicate dinoflagellate contribution. High pristane/phytane ratio (Pr/Ph = 2–4) argue for deposition under oxic conditions.